2009
DOI: 10.4236/health.2009.12012
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofiber-based drug delivery systems

Abstract: Electrospinning is a very simple and versatile process by which polymer nanofibers with diameters ranging from a few nanometers to several micrometers can be produced using an electrostatically driven jet of polymer solution or polymer melt. Significant progress has been made in this process throughout the past few years and electrospinning has advanced its applications in many fields, including pharmaceutics. Electrospun nanofibers show great promise for developing many types of novel drug delivery systems (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(84 citation statements)
references
References 38 publications
(59 reference statements)
1
77
0
1
Order By: Relevance
“…Solventbased electrospinning has been found to be an excellent method also for the preparation of solid dispersions due to the fast and, thus, very efficient amorphization of the drug enclosed in the fibers owing a large surface area Yu et al, 2009). Although various modifications have been published in respect to the ES setup related mostly to the spinneret (e.g., needleless (Molnár and Nagy, 2016), side-by-side or multiaxial electrospinning (Illangakoon et al, 2015;Yang et al, 2016;Yu et al, 2015)), the challenge of increasing the productivity of ES could not have been addressed considering the high output of other fiber formation techniques such as melt blowing (Balogh et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Solventbased electrospinning has been found to be an excellent method also for the preparation of solid dispersions due to the fast and, thus, very efficient amorphization of the drug enclosed in the fibers owing a large surface area Yu et al, 2009). Although various modifications have been published in respect to the ES setup related mostly to the spinneret (e.g., needleless (Molnár and Nagy, 2016), side-by-side or multiaxial electrospinning (Illangakoon et al, 2015;Yang et al, 2016;Yu et al, 2015)), the challenge of increasing the productivity of ES could not have been addressed considering the high output of other fiber formation techniques such as melt blowing (Balogh et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on delivery of various bioactive molecules in sustained manner from a wide range of polymeric nanofibers [1], [18]- [21]. In addition, the polymeric nanofibers could support to encapsulate and also enhances the dissolution of the water insoluble drugs due to its high surface area to volume ratio properties [22], [23]. Furthermore, the drugs chemical integrity properties were not altered by the electrospinning process [23], [24].…”
Section: Resultsmentioning
confidence: 99%
“…Electrospun nanofibers show great promise for developing many types of novel drug delivery systems (DDS), as shown in Figure 2, due to their special characteristics and the simple but useful and effective top-down fabricating process, DDS is focused on drug-loaded nanofiber preparation from pharmaceutical and biodegradable polymers. All types of active pharmaceutical ingredients have been used as model drugs, such as small molecular drug, herbs, proteins, poorly water-soluble and water-soluble drugs, DNA, genes and vaccines [47]. Tissue engineering is one of the most desirable techniques for tissue regeneration.…”
Section: Electrospinning Methodsmentioning
confidence: 99%